Herpesvirus Infections and Childhood Arterial Ischemic Stroke: Results of the VIPS Study - Elkind, Mitchell S. V. (Circulation, 2016)
BACKGROUND: Epidemiological studies demonstrate that childhood infections, including varicella zoster virus (VZV), are associated with an increased risk of arterial ischemic stroke (AIS). Other herpesviruses have been linked to childhood AIS in case reports. We sought to determine whether herpesvirus infections, which are potentially treatable, increase risk of childhood AIS. METHODS AND RESULTS: We enrolled 326 centrally-confirmed cases of AIS and 115 stroke-free controls with trauma (ages 29 days-18 years) with acute blood samples (≤3 weeks after stroke/trauma); cases had convalescent samples (7-28 days later) when feasible. Samples were tested by commercial ELISA kits for IgM/IgG antibodies to herpes simplex virus (HSV) 1 and 2, cytomegalovirus (CMV), Epstein Barr virus (EBV), and varicella zoster virus (VZV). An algorithm developed a priori classified serologic evidence of past and acute herpesvirus infection as dichotomous variables. Median (quartiles) age was 7.7 (3.1-14.3) years for cases and 10.7 (6.9-13.2) for controls (p=0.03). Serologic evidence of past infection did not differ between cases and controls. However, serologic evidence of acute herpesvirus infection doubled the odds of childhood AIS, even after adjusting for age, race, and socio-economic status (OR 2.2; 95% confidence interval, 1.2-4.0; p=0.007). Among 187 cases with acute and convalescent blood samples, 85 (45%) showed evidence of acute herpesvirus infection, with HSV-1 found most often. Most infections were asymptomatic. CONCLUSIONS: Herpesviruses may act as a trigger for childhood AIS, even if the infection is subclinical. Antivirals like acyclovir might have a role in the prevention of recurrent stroke if further studies confirm a causal relationship.